Role of the N‐terminal signal peptide in the membrane insertion of Aquifex aeolicus F1F0 ATP synthase c‐subunit. (20th June 2013) - Zhang, Chunli; Marcia, Marco; Langer, Julian D.; Peng, Guohong; Michel, Hartmut
<x xml:space="preserve">Abstract</x> Rotary ATPases are membrane protein complexes that couple ATP hydrolysis to ion translocation across the membrane. Overall, they are evolutionarily well conserved, but the N‐terminal segments of their rotary subunits (c‐subunits) possess different lengths and levels of hydrophobicity across species. By analyzing the N‐terminal variability, we distinguish four phylogenetic groups of c‐subunits (groups 1–4). We characterize a member of group 2, the c‐subunit from Aquifex aeolicus F1F0 ATP synthase, both in native cells and in a heterologous expression system. We demonstrate that its N‐terminal segment forms a signal peptide with signal recognition particle (SRP) recognition features and is obligatorily required for membrane insertion. Based on our study and on previous characterizations of c‐subunits from other organisms, we propose that c‐subunits follow different membrane insertion pathways.